The Future of Learning by Searching the Web: Mobile, Social, and Multimodal - Kammerer, Yvonne; Brand-Gruwel, Saskia; Jarodzka, Halszka (Frontline Learning Research, 2018)
Recent technological developments related to the World Wide Web including mobile computing, social media, and online videos are shaping the way we learn. As argued in the present commentary, the majority of educational psychological research that has examined how individuals learn by searching the Web, however, has not kept up with this pace. Therefore, the goal of this commentary is to discuss how recent technological developments might affect how learners acquire knowledge through Web search and to provide a respective research agenda. Specifically, we will focus on the use of mobile devices and digital assistants, social networking sites, and online videos, and the opportunities and challenges they present to learners. In addition, we suggest that future research should study the ongoing learning processes during Web search in greater detail. We believe that examining the research questions raised in the present commentary will uniquely contribute to the literature on Web-based searching and learning. MP3 File